The Obstacles in Developing MSMEs in The District of Jagoi Babang - Budiman, Jumardi; Herkulana, Herkulana (Universitas Negeri Semarang, 2021)
The aim of this research was to identify the obstacles in developing MSMEs in the district of Jagoi Babang. The approach used in this research was descriptive qualitative in which the instruments of data collecting were interview, observation sheets, and documentary study. The sources of data in this research were 16 (sixteen) Bidai craftsmen, the stakeholders from the Department of Cooperative, SME, Labour and Transmigration that represented by the chief of development section of MSMEs. The techniques of data analysis were data reduction, data display and conclusion drawing or verification. The findings of the study showed that the obstacles in developing MSMEs on Bidai craft in Jagoi Babang, Bengkayang regency, were the entrepreneurs did not have business license, facing difficulties in accessing the capital aid, lack of managerial competence, lack in using the modern technology in the production and marketing process that impacted to the turnover and the profit could not be increased.